Penambahan Biochar Berbasis Limbah pada Inceptisol terhadap Budidaya Tembakau (Nicotiana tabacum (L.)) Varietas Kemloko di Temanggung - Katon, Damarmoyo Sasongko; Susilo, Buana; Dalimartha, Lengga Nurullah; Wiguna, Eko Chandra; Isdiantoni, Isdiantoni; Koentjoro, Maharani Pertiwi; Prasetiyo, Endry Nugroho (Universitas Sebelas Maret, 2017)
Biochar is a biological charcoal derived from incomplete combustion (pyrolysis) of agricultural residualmaterials that can increase carbon sustainably, retention of water and nutrients in soil. This research aimed todemonstrate the effect of adding biochar on inceptisol for Kemloko tobacco cultivation in Temanggung, CentralJava, Indonesia. The data analysis of this research was using Factorial Random Design with two factors(treatment and dose). The results showed that the addition of biochar + compost increase productivity of 491.6kg/ha comparing to the control with the higher tobacco quality. Chemical analysis of the respected soil showedthat the biochar + compost treatment increase pH level up to 5.46 with the organic matter level and total nitrogenas well increased about 2.66% and 0.180% respectively.